2020
DOI: 10.3390/molecules25173899
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Mesoporous Silica Materials: A Review on Synthetic Strategies and Applications

Abstract: Because of its tunable textural properties and chirality feature, chiral mesoporous silica (CMS) gained significant consideration in many fields and has been developed rapidly in recent years. In this review, we provide an overview of synthesis strategies for fabricating CMS together with its main applications. The properties of CMS, including morphology and mesostructures and enantiomer excess (ee), can be altered according to the synthetic conditions during the synthesis process. Despite its primary stage, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 113 publications
0
16
0
Order By: Relevance
“…Properties of these materials can be manipulated further through functionalization of the organic molecules to produce mesoporous silica with large chiral internal surface area (33). These examples and others in a review by Cui et al (34) show that chirality in mesoporous silica can be induced through a variety of synthetic pathways involving both chiral and achiral SDA.…”
Section: Porous Functional Silica Structures and Their Synthesismentioning
confidence: 97%
“…Properties of these materials can be manipulated further through functionalization of the organic molecules to produce mesoporous silica with large chiral internal surface area (33). These examples and others in a review by Cui et al (34) show that chirality in mesoporous silica can be induced through a variety of synthetic pathways involving both chiral and achiral SDA.…”
Section: Porous Functional Silica Structures and Their Synthesismentioning
confidence: 97%
“…Nevertheless, these materials have been successfully tested for the enantioselective resolution and adsorption of chiral compounds, for the delivery of chiral drugs, and for chromatographic separations. 1489 More relevant to this review, a helical mesoporous silica has been shown to, by virtue of the homohelicity of its structure, enantioselectively promote the asymmetric production of pyrimidyl alkanol from diisopropylzinc (i-Pr2Zn) and pyrimidine-5-carbaldehyde. 1490 In another case, similar materials were shown to add diaestereoselectivity to the Mannich reaction (Figure 107).…”
Section: Mesoporous Materialsmentioning
confidence: 99%
“…One particularly curious type of shape selectivity uses chiral mesoporous materials to introduce enantioselectivity in catalytic reactions. The synthesis of chiral mesoporous materials has constituted a challenge in itself, and is a field still in its infancy. Moreover, most of the few chiral mesoporous materials available to date are unstable, a fact that limits their application. Nevertheless, these materials have been successfully tested for the enantioselective resolution and adsorption of chiral compounds, for the delivery of chiral drugs, and for chromatographic separations .…”
Section: Novel Nanostructures: Oxides Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica-based chiral materials such as helical mesoporous silica have attracted considerable attention in the fields of catalysis, templating, and chiral recognition. These materials are prepared by sol–gel transcription using an organic chiral structure as a template. This process is generally tedious, requiring many steps and long reaction times. Moreover, the chemical reaction leads to an aggregated structure approximately few μm to 100 nm in length with a 2–3 nm helical pore.…”
mentioning
confidence: 99%